AF UPRAKTISKE GRUNDE: Om samlinger blandt danske musikfans - Vaaben, Nana (Tidsskriftet Antropologi, 2001)
The article is a study of music fans and primarily concerns the objects collected by these people. Two main arguments run through the analysis. First of all, the collections are considered as results of a human eagerness to categorize and systematize, and, as such, one can see this accountn as an exemplification of Claude Lévi-Strauss’ thought in a modern Western setting: Things are not known because they are relevant – they become relevant because they are known; as soon as a possible acquisition is discovered by a fan, comes the urge to obtain it. Such conclusions, more-over, are much in line with Baudrillard’s writings on collections, in which system-atisation and striving for completing a known series are the basic motives for collecting. There are things, however, which are difficult to explain by reference to the urge for completeness, for example, those things which have previously been used, or merely touched, by a particular singer. The second and prominent part of the article’s argument explores, therefore, other theo-retical possiblities for understanding the music fans’ collections. Classical theories of magic and theories of play and frames are combined to show how fans seek to gain allegorical control – not of themselves, as is suggested by Baudrillard – but of a social relation that has been bodily felt through listening to music. The fans and collectors define their use of symbols in ways that resemble the classical anthropologies of magical practice within a frame of play. Furthemore, an analysis of autographs will show that, while allegorical micro universes and the rules and systems within them are much valued by fans, many also seek to obtain proof that the felt relation to a given singer actually exists outside the frame of play. The autograph can thereby be considered a gift, and the cultural rules guiding the interpretation of this gift are not confined to a universe of play. The autographs are interpreted according to well-established cultural ideas of gifts as expressions of emotions. One regards the autograph as a gift and, especially, as a veritable sign that the fan exists in the conscious world of the singer. It is argued that, for the music fan, collecting is not merely an attempt to gain control of the self through striving for completeness, but an attempt to gain control of a particular social relation which is difficult to handle, making it necessary to jump back and forth between play and “reality” and between the corresponding ways of using symbols within these different contexts.